2017
DOI: 10.1128/jvi.01911-16
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus nsp1α Inhibits NF-κB Activation by Targeting the Linear Ubiquitin Chain Assembly Complex

Abstract: Linear ubiquitination, a newly discovered posttranslational modification, is catalyzed by the linear ubiquitin chain assembly complex (LUBAC), which is composed of three subunits: one catalytic subunit HOIP and two accessory molecules, HOIL-1L and SHARPIN. Accumulating evidence suggests that linear ubiquitination plays a crucial role in innate immune signaling and especially in the activation of the NF-B pathway by conjugating linear polyubiquitin chains to NF-B essential modulator (NEMO, also called IKK␥), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 73 publications
1
24
0
1
Order By: Relevance
“…Previous studies have shown that PRRSV infection inhibits NF-B activation (32,33). However, in this study, we found that PRRSV infection activated NF-B and cathepsin At 24, 36, and 48 hpi, cell surface expression levels of HS (C) and PRRSV N protein (G to I) were determined by flow cytometry and Western blotting, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that PRRSV infection inhibits NF-B activation (32,33). However, in this study, we found that PRRSV infection activated NF-B and cathepsin At 24, 36, and 48 hpi, cell surface expression levels of HS (C) and PRRSV N protein (G to I) were determined by flow cytometry and Western blotting, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, recent research showed that the protein encoded by ORF61 in SVV and VZV prevents ubiquitination and degradation of IκBα, thereby suppressing NF-κB-mediated immune responses [65]. Moreover, Jing et al reported that reproductive and respiratory syndrome virus (PRRSV) nsp1α inhibits NF-κB activation by targeting the linear ubiquitin chain assembly complex [66]. It resulted in the reduction of the linear ubiquitin chain assembly complex dependent linear ubiquitination of NF-κB essential modulator (NEMO), revealing an additional mechanism of immune modulation by PRRSV [66].…”
Section: Viral Immune Evasionmentioning
confidence: 99%
“…Moreover, Jing et al reported that reproductive and respiratory syndrome virus (PRRSV) nsp1α inhibits NF-κB activation by targeting the linear ubiquitin chain assembly complex [66]. It resulted in the reduction of the linear ubiquitin chain assembly complex dependent linear ubiquitination of NF-κB essential modulator (NEMO), revealing an additional mechanism of immune modulation by PRRSV [66]. Additionally, some viruses such as HSV and cytomegalovirus have evolved mechanisms that inhibit necroptosis to overcome host antiviral defences.…”
Section: Viral Immune Evasionmentioning
confidence: 99%
“…For example, Du et al (18) reported that the highly pathogenic porcine reproductive and respiratory syndrome virus Nsp1␣ replicating protein can target swine leukocyte antigen class I molecules for proteasomal degradation. Jing et al (19) found that LUBAC-induced NF-B and proinflammatory cytokine expression can be inhibited in the early phase of PRRSV infection. Mechanistically, Nsp1␣ binds to HOIP and HOIL-1L and impairs the interaction between HOIP and SHARPIN, thus reducing the LUBAC-dependent linear ubiquitination of NEMO.…”
mentioning
confidence: 99%